Understanding Relationships and Remittance Flow During the Migration Period: Strength of Social Ties as a Factor Determining Remittance Behaviour - Mukwembi, Thebeth, R; Maharaj, Pranitha (African Human Mobility Review, 2021)
Remittances transferred between migrants and non-migrants play a major rolein alleviating poverty and improving social and economic well-being in manydeveloping countries. Although remittances are regarded as an outcome ofmigration with far reaching effects as a livelihood strategy, not all non-migrantswith migrant family members are recipients of remittances. Remittances are nottransferred to all non-migrant family members in the country of origin. Migrantsidentify particular individuals as recipients of remittances, which they send totheir home countries during the migration period. Therefore, it is important tounderstand the determinants of remittance flow and remittance behaviourduring the migration period. This study explores relationships between migrantsand non-migrants and how such relations influence the flow of remittancesduring the migration period. A qualitative approach was employed in which 60interviews were conducted (30 with Zimbabwean migrants in Durban and 30with their respective family members in Zimbabwe). The study found that thestrength of social ties between migrants and non-migrants plays a major role indetermining remittance flows.